2015
DOI: 10.1177/1363459315574116
|View full text |Cite
|
Sign up to set email alerts
|

Integration of acupuncture into conventional medicine from health professionals’ perspective: A thematic synthesis of qualitative studies

Abstract: Acupuncture is a prominent Complementary Medicine. Although health professionals' conceptions of acupuncture may affect its utilisation and integration within conventional medicine, these aspects have not been well studied. The aim of this review was to analyse the integration of acupuncture into conventional medicine from the perspective of health professionals. We conducted a systematic review and a thematic synthesis of qualitative studies that analysed the integration of acupuncture into conventional medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 62 publications
(237 reference statements)
3
13
0
Order By: Relevance
“…Moreover, the mechanistic vision of human beings in which the biomedical approach is based explained illness in terms of external toxic agents or malfunctioning of the organism (Goswami, 2008). Healthcare professionals seek to overcome this approach, which is consistent with other studies that underline the motivation of health professionals to enrich their vision of health considering other paradigms (García-Escamilla et al, 2015;Yeh et al, 2008). In this concern, our results support other studies that relate the benefits of acupuncture not just to improvements in physical symptoms but also in the emotional state, quality of life and well-being (Deng and Cassileth, 2009;Deng et al, 2004;Kemper et al, 2000;Vas et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, the mechanistic vision of human beings in which the biomedical approach is based explained illness in terms of external toxic agents or malfunctioning of the organism (Goswami, 2008). Healthcare professionals seek to overcome this approach, which is consistent with other studies that underline the motivation of health professionals to enrich their vision of health considering other paradigms (García-Escamilla et al, 2015;Yeh et al, 2008). In this concern, our results support other studies that relate the benefits of acupuncture not just to improvements in physical symptoms but also in the emotional state, quality of life and well-being (Deng and Cassileth, 2009;Deng et al, 2004;Kemper et al, 2000;Vas et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, there are few studies that explore in detail the motivations of health professionals to study and practise acupuncture in Western countries. These motives have been recently collected in a qualitative systematic review (García-Escamilla et al, 2015). Accordingly, nurses underline the opportunity to develop themselves in a personal and professional way due to the emphasis on care and holistic healing (Johannessen, 2009(Johannessen, , 2011, while physicians associate their motivations with convictions, individual experiences on the effectiveness of acupuncture and personal knowledge (Marian et al, 2006;Rayner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study comprised four stages: (1) a systematic search of key databases, (2) record retrieval and screening for relevance, (3) critical appraisal, (4) thematic synthesis as described by Thomas and Harden (2008). This technique has been widely used by researchers to gain a deeper insight into HCPs' experiences within the health care system [46,47].…”
Section: Methodsmentioning
confidence: 99%
“…[35][36][37][38] The Academic Consortium of Integrative Medicine and Health lists more than 60 academic centers and their affiliates as members, 39 with many of the centers including alternative therapy options, such as meditation, massage, and acupuncture. 40,41 In addition, formal surveys of medical staff members have revealed a substantially positive attitude toward what was once considered a fringe field. [42][43][44] The BMC needs assessment showed that high regard and acceptance for the existing pediatric acupuncture service made it very likely to succeed as a core service offered in the Pediatric Pain Clinic.…”
Section: Discussionmentioning
confidence: 99%